The Relationship Between the Functional and Physical Condition with Pain and Trauma of Basketball Players in Terms of Gender - Ernestas Barkus; Ligita Šilinė (Lithuanian Sports University, 2023)
Background. Lower extremity injuries account for more than half of the trauma experienced by basketball players. With a high number of trauma, it is important to include trauma prevention programs and monitor the physical and functional condition of the players. It is not clear what is the relationship between the functional and physical condition with pain and trauma of basketball players in terms of gender. The aim. To determine the relationship between the functional and physical condition with pain and trauma of basketball players in terms of gender. Methods. 20 basketball players (10 boys and 10 girls) participated in the study. Information about trauma and training status of basketball players was collected through a questionnaire. The functional status of the subjects was assessed with the Functional Movement Screen and the Y Balance Test. The physical condition was assessed by: Ely's (for the length of the rectus femoris muscle), Thomas (for the length of the iliopsoas muscle), and Pendulum (for the mobility of the spine) tests. Pain intensity was assessed on a numeric pain intensity scale. Results. In female players, a moderate inverse relationship was found between functional condition and pain (r = -0.679, p<0.05), and a strong relationship with trauma (r = -0.898, p<0.05) was found. For male players, the relationship between functional condition and pain and trauma was not established (r=-0.460, p>0.05 and r=-0.571, p>0.05, respectively). An inverse relationship was established between the length of the iliopsoas muscle in females and pain (r=-0.661, p<0.05) and trauma (r= -0.500, p>0.05). The relationship between the length of the rectus femoris muscle and pain was found in both males (r=-0.687, p<0.05) and females (r=-0.887, p<0.05), and the relationship with trauma was found only in females (r=- 0.816, p<0.05). Conclusions. The functional and physical condition of female basketball players is more related to the intensity of pain and trauma than that of male basketball players. Keywords: Functional movement, muscle length, basketball, trauma, gender.